The Effect of Authentic Leadership on Nurses' Trust in Managers and Job Performance: A Cross-Sectional Study - Bayan Alilyyani (MDPI AG, 2022)
Background: Nurse leaders have the responsibility to build healthy work environments for staff nurses and enhance nurses' outcomes. Authentic leadership is one of the leadership theories that have been shown to have positive impacts on nurses' outcomes. The goal of this study was to test the effect of authentic leadership on trust in managers and job performance among nurses in Saudi Arabia. Methods: A non-experimental, cross-sectional design was applied. A total of 116 nurses who met the inclusion criteria completed the survey. To test the study variables, three different scales were used. The data in this study were analyzed using SPSS version 28.0.1.1. Results: The findings of this study showed that there were significant and positive effects of authentic leadership and its four components on trust in managers. However, no relationships were found between authentic leadership and its four elements, and job performance. Conclusions: Authentic leaders have the ability to improve work environments by building a trustful relationship with nurses. This study focuses on the role of authentic leadership in nursing practice and its essential effects to enhance the work environments. It also provides future researchers in Saudi Arabia with comprehensive knowledge about conducting studies of authentic leadership in nursing and examine its effects on outcomes related to nurses.